Character Ambivalence In Facing Social Changes In Shifu Becomes Dumb And Dumber By Mo Yan - Tanriwa, Arkan; Wuryandari, Nurni W. (KnE Social Sciences, 2017)
Social and societal changes, and the essential ambivalence of the everyman in face of those changes is the theme and major narrative thread in the short story Shifu Becomes Dumb and Dumber (师傅越来越幽默: Shifu Yuelaiyue Youmo) by contemporary Chinese author Mo Yan. In Shifu, Mo Yan relays the theme by tracing the life of the main character. The theme’s logical conclusion is achieved through humor and detailed narratives of the idiosyncrasies of that main character. To provide granularity and dimension for the behaviors, thoughts and lifestyle of that character, the author introduces a minor character for contrasting effect, that brings the 'dumb and dumber' to the fore. The way the author describes Ding’s idiosyncratic ways and juxtaposes them with those of the minor character, with the specific scenes as the narrative backdrop, competently and critically portrays the life and living of the essential everyman in China in the face of society undergoing rapid and fundamental sociocultural flux Keywords: Shifu Becomes Dumb and Dumber short story, character analysis, social change in China